A New Magnetically Retrievable Porous Supported Catalyst for The Suzuki‐Miyaura Cross‐Coupling Reaction. Issue 37 (7th October 2020) - Rahimi, Leila; Mansoori, Yagoub; Nuri, Ayat; Esquivel, Dolores
Abstract: Magnetic mesoporous silica composite (MNP@SiO2 ‐SBA) was obtained via embedding magnetite nano‐particles (MNPs) between SBA‐15 channels. It was functionalized with N‐(3‐(trimethoxysilyl)propyl)picolinamide (TMSP‐PCA) and then complexed with Pd(II). The obtained supported Pd(II) catalyst (MNP@SiO2 ‐SBA‐PCA) was characterized by conventional methods. The prepared magnetic catalyst showed high activity in the Suzuki‐Miyaura reaction under optimal reaction conditions, including solvent, amount of catalyst, base, and temperature. Aryl bromides and iodides showed better results than aryl chlorides. Phenylboronic acid showed enhanced reactivity in compared with 4‐methylphenylboronic acid, and the catalyst exhibited a noticeable stability and re‐used several times after magnetic separation. Abstract : The present work, describes the of magnetic mesoporous silica (MNP@SiO2 ‐SBA) followed by functionalization with N‐(3‐(trimethoxysilyl)propyl)picolinamide (TMSP‐PCA) and the complexed with Pd(II). The obtained supported magnetic catalyst showed high activity in the Suzuki‐Miyaura coupling reaction. The reaction conditions including solvent, amount of catalyst, base, and temperature were optimized, and the catalyst was recycled and reused six times after magnetic decantation, washing and drying steps without significant loss of reactivity.